BLOOM MART A DYNAMIC WEBSITE USING MERN STACK (International Journal of Food and Nutritional Sciences, 2022)
Bloom Mart is a easy to use website developed using MERN stack (MongoDB, Express. js, React. js and Node. js) which helps in plan for decorations for events such as engagement, wedding, haldi functions and so on. Bloom Mart is a new concept of an online application that helps to choose and organize decorations for every type of event. The service providers in this case are the organizers who are in charge of decorations and other schedules and they use an integrated calendar that is equipped with notification features in order to improve work flow. It also allows users to explore different themes and decorations, read detailed information about the providers and their services, and thus easily book the desired decoration for the event.